Implementation of web-based motorcycle workshop management application to improve efficiency and service quality - Adhiatma, Novri; Ikhsan, Muhammad; Purnama, Fery; Magfira, Fortia (Universitas Trunojoyo Madura, 2025)
The purpose of this study is to create a web-based motorcycle workshop management application that can improve operational efficiency and quality of service provided by workshops. Many motorcycle workshops still use manual systems. This causes many problems, such as errors in recording service history, inaccuracy in managing spare part stock, and difficulty in setting customer service schedules. To solve these problems, this application is designed using the rapid application development (RAD) method, this method allows application development to be carried out quickly and involves users in every stage. The Black Box Testing method is used to test the functionality of the application without examining the internal structure of the code. The test results show that all the main features of the application login, spare part management, service transaction recording, product search, out of stock notification, receipt printing, and logout run well. In addition, performance testing shows that the application can handle a large user load without crashing and has a response time of less than 3 seconds. It is expected that this application will help workshops record motorcycle maintenance history, monitor stock in real-time, and increase customer satisfaction by providing faster, more precise, and more organized services.Keywords: Web Application, Black Box Testing, Operational Efficiency, Motorcycle Workshop Management, Rapid Application Development